Made in Italy [videorecording (DVD)] - D'Arcy, James, 1975-; Neeson, Liam; Richardson, Micheál; Bilello, Valeria, 1982-; Duncan, Lindsay (Shout! Factory, 2020)
A heartwarming father-son story set in glorious Tuscany about bohemian London artist Robert, who returns to Italy with his estranged son Jack to make a quick sale of the house they inherited from his late wife. Neither expects to find the once beautiful villa in such a state of disrepair. Renovations go badly, with father and son soon finding themselves at odds. Robert's comical lack of DIY experience leads him to seek help from some colorful locals.